2014
DOI: 10.1093/icesjms/fsu093
|View full text |Cite
|
Sign up to set email alerts
|

Biomass consumption by breeding seabirds in the western Indian Ocean: indirect interactions with fisheries and implications for management

Abstract: Fisheries potentially affect seabirds both directly and indirectly. Well-documented direct effects have resulted in significant losses to seabird populations, but indirect effects are less well known. One way in which tropical seabirds may be indirectly affected is through overexploitation of large subsurface predators. Tropical seabirds must forage over wide areas to attain sufficient prey and have evolved various methods of increasing foraging efficiency. One strategy is their association with surface-feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…This study is the first to describe the non-breeding movements and behavior of sooty terns, a seabird species considered to be the world's most abundant with a correspondingly high consumption of marine resources (Brooke, 2004;Danckwerts et al, 2014). Our data revealed that Bird Island sooty terns dispersed widely over the Indian Ocean north of c. 25 • S, although individuals appeared to migrate to similar geographical areas in consecutive nonbreeding seasons.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study is the first to describe the non-breeding movements and behavior of sooty terns, a seabird species considered to be the world's most abundant with a correspondingly high consumption of marine resources (Brooke, 2004;Danckwerts et al, 2014). Our data revealed that Bird Island sooty terns dispersed widely over the Indian Ocean north of c. 25 • S, although individuals appeared to migrate to similar geographical areas in consecutive nonbreeding seasons.…”
Section: Discussionmentioning
confidence: 76%
“…Our finding that different individuals of the Bird Island population utilize different core areas during the non-breeding period, and yet another area for the pre-laying exodus, shows that the birds can be vulnerable to adverse conditions far from the breeding colonies. These can include excessive commercial exploitation of pelagic predatory fish, especially tuna (Pillai and Satheeshkumar, 2013;Danckwerts et al, 2014). The most used core area, the Bay of Bengal, is highly contaminated by industrial pollutants and by plastic microparticles (Eriksen et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Despite a lack of information on population trend they have been assigned a conservation status of 'Least Concern' (IUCN 2015), presumably because they are regarded as sufficiently numerous. However, the total population size of Sooty Terns is reported to be falling (Schreiber et al 2002) most likely because of the combined threats of over-exploitation of pelagic fish species (upon which they are dependent for successful foraging) (Danckwerts et al 2014), climate change (Foden et al 2013), and egg harvesting (Feare et al 2007).…”
Section: Conservation Status Of Sooty Ternsmentioning
confidence: 99%
“…Therefore, when they numerically dominate breeding seabird communities (as Sooty Terns once did and still do on Ascension Island), they can deplete pelagic small fish reserves markedly. For example, Danckwerts et al (2014) found that the breeding seabird population of the western Indian Ocean numbered 19 million birds, of which 85% numerically comprised Sooty Terns. They calculated that the seabird population consumed between 150,000 and 500,000 metric tons of prey with 81% of consumption by Sooty Terns.…”
Section: Impacts Of Sooty Tern Population Decline On the Marine Ecosymentioning
confidence: 99%
“…With an estimated breeding population size of 19 million individuals [ 11 ], seabirds represent the most abundant and widespread avifauna in the Western Indian Ocean [ 12 ]. The islands of this region are major breeding sites for terns (order Charadriiformes) as well as species in the orders Phaethontiformes (tropicbirds), Procellariformes (petrels and shearwaters), and Suliformes (boobies and frigatebirds).…”
Section: Introductionmentioning
confidence: 99%